Blood doping at the Olympic Games - Fitch, K. D. (The Journal of Sports Medicine and Physical Fitness, 2017)
INTRODUCTION: The objective of this paper was to review our knowledge of athletes who have, are believed to have or have attempted to engage in blood doping to enhance their performance at an Olympic Games.